AN ANALYSIS OF FIGURATIVE LANGUAGES ON ROBERT FROST POEMS THE ROAD NOT TAKEN AND STOPPING BY WOODS ON A SNOWY EVENING: A REFLECTION OF AMERICAN CULTURE IN GENERAL - Nanda Husaini; Silvi Listia Dewi (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2021)
Literature is a product of thoughts, ideas, concepts, and also imagination which are the reflection of the life around the author. Poetry as one type of literary work is arguably unique and different compared to other types of literary works. This is because of the figurative language that surrounds a poem that creates the meaning implied in the literal meaning. This research is intended to find out what kind of figurative language is used in Robert Frost's selected poems based on Perrine’s theory, so that we can find out the implicit meaning of the two poems. The whole process is carried out using the desk observation research method, where primary data and secondary data are collected to understand the entire research object. The results of the analysis process show that Robert Frost uses metaphor, symbol, personification, and simile in the poem “The Road Not Taken”. Whereas in the poem “Stopping by Woods on a Snowy Evening”, Frost uses metaphor, symbol, personification, and hyperbole. From these results, the implied meaning of the two poems is revealed. Where “The Road Not Taken” describes Individualism and its influence on the “decision making” process, while “Stopping by Woods on a Snowy Evening” illustrates the level of self-consistency. Both of these poems describe the culture of American society in general.